A Women-Centric Approach: Key to Satisfaction With Agency Services. Issue 2 (May 2019) - Wilson, Bincy
Involvement of women in commercial sexual activity (CSA) has always been viewed from a moralistic point of view in India, with legislations attempting to rescue and rehabilitate them. Some, however, look at this involvement as legitimate work. Agencies engaged in service provision align themselves to these differing ideologies. This article examines the organizational frameworks and ideologies of agencies engaged in service provision to women in or exiting from CSA, along with assessing women's level of satisfaction and the duration of services received from these agencies. In doing so, 40 service providers from nine agencies across five major cities in India were interviewed, and 163 women receiving services from these agencies participated in a survey. The findings revealed that agencies differed based on their guiding principles, factors determining services, structure, involvement of peers/survivors, and decision-making process. The level of satisfaction with services, and duration of services received, was the highest for those in women-centric agencies and the lowest in government state protective homes. Agencies assisting women in CSA must consider adopting non-institutional-based and women-centric service approaches, as this would make a real difference to those being assisted.